Synthesis of the 1,5-disubstituted tetrazole-methanesulfonylindole hybrid system via high-order multicomponent reaction - Aguilar-Morales, Cesia M.; Frías-López, América A.; Emilio-Velázquez, Nadia V.; Islas-Jácome, Alejandro; Granados-López, Angelica Judith; Araujo-Huitrado, Jorge Gustavo; López-Hernández, Yamilé; Hernández-López, Hiram; Chacón-García, Luis; López, Jesús Adrián; Cortés-García, Carlos Jesús (Beilstein Journal of Organic Chemistry, 2024)
A series of 1,5-disubstituted tetrazole-indole hybrids were synthesized via a high-order multicomponent reaction consisting of an Ugi-azide/Pd/Cu-catalyzed hetero-annulation cascade sequence. This operationally simple one-pot protocol allowed high bond-forming efficiency and creating six new bonds (two C–C, three C–N, and one N–N). Additionally, the products were evaluated against breast cancer MCF-7 cells, finding moderate activity in the compounds substituted with fluorine and chlorine.
Keywords: 1,5-disubstituted tetrazoles; high-order multicomponent reaction; isocyanides; MCF-7 cell line; methanesulfonylindoles; Ugi-azide reaction